(untitled) (Fiep Bulletin - online, 2016)
The purpose of this research was to gather information of the performance of physical education teachers (EFI) in the practical field with the students who are overweight and / or obesity and to survey the specific measures that they have adopted or may adopt in their classes as a strategy to support the actions of preventing and combating this public health problem. The main purpose was to collect data on the views and possible interventions that EFI teachers do or could do with their students in overweight status and / or obesity. Participated in this study a sample of 234 EFI professionals all considered active in preventing and combating overweight and / or obese. It was sent via e-mail one SurveyMonkey questionnaire to 617 EFI professionals. The questionnaire of 64 questions was based on the Belgian questionnaire developed by the Department of Sport Sciences University of Liege. This research showed that in fact there is an imbroglio involving practical actions related to the control and overweight combat and obesity by professionals of EFI interviewed together to their students.